Reframing Cross-Border Cybercrime Investigations: The Digital Evidence Paradox, Individual Rights, And Rebuilding Sri Lanka’s Legal Framework - Fernando, M.B.I.N. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
Contemporary cybercrime investigations expose a structural contradiction between digital technology and procedural based legal system. Since cybercrime investigation increasingly depend on transnational digital evidence prevailing legal framework is territorially limited and remains procedurally inadequate. This gap creates barriers for a robust investigation process while bringing into focus serious concerns on individual rights, including privacy and due process. Existing mechanisms, including mutual legal assistance procedures and timely investigations remain slow and procedurally inadequate, Furthermore, one of the key challenges in cross-border cybercrime investigations is the admissibility and timely use of digital evidence in Sri Lankan courts. Despite provisions under the Computer Crimes Act No. 24 of 2007 (Amended) and the Evidence Ordinance, digital evidence often faces delays due to authentication and preservation concerns. The digital evidence paradox thus highlights the systemic conflict between operational necessity and normative safeguards in cross-border cybercrime enforcement. The purpose of this study is to assess the limitations of Sri Lanka’s Computer Crime Act in structuring cross-border digital evidence and to advance a rights-based framework for effective international cooperation and compliance with human rights standards. This study adopts a qualitative research methodology combining doctrinal legal analysis examining relevant international and domestic legal instruments. To supplement this analysis this study, incorporate semi-structured interviews with law enforcement officers, legal practitioners and policy experts. To enhance the investigative effectiveness in regulating cross-border digital evidence investigations and international cooperation while safeguarding individual rights this study examines the limitations in Sri Lanka’s legal framework in comparison with the United States of America’s legal framework. In comparative perspective with the United States of America, particularly its Clarifying Lawful Overseas Use of Data Act 2018 and data-sharing mechanisms, which provide a model for cross-border digital evidence access. Accordingly, this paper identifies best practices for harmonizing cybercrime enforcement and human rights protection.
Keywords: Transnational digital evidence; Cross-border cybercrime; Mutual legal assistance; Human rights safeguards